The differential impact of network connectedness and size on researchers' productivity and influence. Issue 5 (15th April 2020) - Hayat, Tsahi; Dimitrova, Dimitrina; Wellman, Barry
ABSTRACT: We analyze the effect of different types of online and offline ties – acquaintanceship, advice, and co-authorship – on researchers' productivity and influence. Unlike static studies of networked work, we look at how changes in these networks affected researchers' performance and influence. Using the number of publications as an indicator of productivity and the number of citations as an indicator of influence, we investigate when researchers were more productive and influential. We study whether their networks were cohesive, if the researchers were central in their networks or linked to central players, and whether their work had more opportunities to be disseminated through diverse, non-redundant ties. Although the connectedness of their networks was positively associated with the researchers' productivity, it was the non-redundant effective size of the networks that was positively associated with the researchers' influence.